Ghana integrated to the world economy: Focus on Ghana-UK-Germany trade linkage model - Daniel Bruce Sarpong (Hamburg Institute of International Economics (HWWA), 1998)
In this study of Ghana integrated to the world economy, we focus primarily on Ghana-UK-Germany trade axis partly because of Ghana's relative dependence on the EU for her international trade. The study employs ,,representative“ country macroeconometric models of these economies, using data over 1970-1991, including bilateral trade links among them and with the USA and Japan, to quantitatively analyze and draw policy inference of the international transmission mechanism of macroeconomic disturbance effects in the trade axis. Specifically, the study addresses the issue: how does external economic perturbations in the EU in particular influence Ghana's policy goals of GDP and bilateral export growth, the nominal current account and inflation; and, which Ghanaian fiscal policy instruments are most influential in enhancing these policy goals in the liberalized world economy. The Ghanaian side of the model developed is characterized by interaction of supply components of agriculture, industry and services and the demand components of gross domestic expenditures, implicitly considering the input-output type of production process. Thus supply-side responses are incorporated into the Ghanaian model since output growth is a major determinant of exports and is relevant for the Ghanaian side of the trade linkage. The economies in the model are linked through trade flows and prices. Ghana is not an export competitor to UK, Germany, USA or Japan. However, she competes with other non-oil developing economies in the markets covered here. Hence Ghana's export price relative to the non-oil developing countries are crucial in the Ghanaian trade flows. Real exchange rates confronting Ghanaian export, foreign import and export price as well as domestic price structures influence Ghana's export price and are factored into the Ghanaian model. In addition the interaction of an aggregated export and import tax are brought explicitly into the model.
Keywords: 330; Internationale Wirtschaftsbeziehungen; Konjunkturzusammenhang; Ökonometrisches Makromodell; Schätzung; Ghana; Deutschland; Großbritannien